Overexpression of CXCL14 Alleviates Ventilator-Induced Lung Injury through the Downregulation of PKM2-Mediated Cytokine Production - Rui Zhu; Yan-Qing Lei; Dong-Chi Zhao (Hindawi Limited, 2020)
Ventilator-induced lung injury (VILI) is one of the most common complications of mechanical ventilation (MV), which strongly impacts the outcome of ventilated patients. Current evidences indicated that inflammation is a major contributor to the pathogenesis of VILI. Our results showed that MV induced excessive proinflammatory cytokine productions together with decreased CXCL14 and increased PKM2 expressions in injured lungs. In addition, CXCL14 overexpression downregulated PKM2 expression and attenuated VILI with reduced inflammation. Moreover, the overexpression of PKM2 markedly diminished the protective effects of CXCL14 against VILI as reflected by worsened morphology and increased cytokine production, whereas PKM2 knockdown decreased cytokine production and attenuated VILI. Collectively, these results suggested that CXCL14 overexpression attenuates VILI through the downregulation of PKM2-mediated proinflammatory cytokine production.